Perencanaan Kebutuhan Tenaga Pendidikan Berbasis Kebutuhan Berkelanjutan: Tinjauan Strategis untuk SMP IT PAPB Semarang - Tommy Candra Hermawan; Ery Handayani; Siti Naviah Nurhayati; Agus Yusuf; Ngurah Ayu Nyoman Murniati (Universitas Muhammadiyah Bangka Belitung, 2026)
Quality education depends not only on the strength of its curriculum but also, and more importantly, on the institution’s ability to ensure the availability of competent educators who meet the specific needs of the school. In integrated Islamic schools such as SMP IT PAPB Semarang, planning for teacher requirements presents more complex challenges because it must accommodate two curricula simultaneously: the national curriculum and the Islamic/diniah curriculum. Therefore, this study aims to formulate a strategic framework for sustainable, needs-based teacher workforce planning that is relevant for middle-level integrated Islamic schools. This research employs a Systematic Literature Review (SLR) method by examining national and international scholarly articles related to educational human resource planning, teacher needs analysis, quality sustainability, and professional development of educators. The synthesis process was conducted by identifying major themes, including needs analysis and long-term projections, comprehensive HR management cycles, strengthening multidisciplinary teacher competence, retention strategies, and institutional adaptability to technological and policy changes. The findings indicate that sustainable teacher workforce planning requires the integration of internal school data, student growth projections, the needs of both general and religious teachers, and prioritized development of holistic competencies. This planning model provides strategic benefits for schools, particularly in maintaining quality continuity, meeting national standards, and reinforcing the distinct characteristics of integrated Islamic education. The resulting strategic framework is expected to serve as a practical reference for other integrated Islamic schools in developing adaptive, sustainable, and future-oriented human resource planning.